Digital Diplomacy and the Transformative Role of Social Media in Contemporary Foreign Policy - Muhammad Ammar (Journal of Religion and Society, 2026)
Digital diplomacy has significantly transformed the practice of foreign policy by incorporating social media platforms into diplomatic communication and engagement strategies. This paper explores how platforms such as Twitter and Facebook enable governments to interact directly with global audiences, disseminate information rapidly, and shape international narratives. The study adopts a qualitative approach, analyzing case studies of state-led digital campaigns and diplomatic interactions to evaluate the effectiveness of social media in advancing national interests. It highlights how digital tools enhance transparency, crisis communication, and public diplomacy while reducing traditional barriers in international engagement. At the same time, the research identifies key challenges, including the spread of misinformation, cyber security risks, and the potential for diplomatic miscommunication due to the immediacy of online platforms. The findings suggest that digital diplomacy is redefining traditional diplomatic practices by prioritizing speed, accessibility, and audience engagement. The paper concludes that social media has become an indispensable instrument in contemporary foreign policy, requiring states to adopt adaptive strategies to navigate the evolving digital landscape effectively. Keywords: digital diplomacy, social media, foreign policy, intemational communication, public diplomacy, cyber risks https://doi.org/10.5281/zenodo.20024529